2013
DOI: 10.1080/02699931.2013.867835
|View full text |Cite
|
Sign up to set email alerts
|

The effect of evaluation on co-occurrence memory judgement

Abstract: Three experiments tested the effect of an attitude towards an object on the memory judgement of whether this object co-occurred with positive versus negative stimuli. We induced positive or negative attitudes towards novel male stimuli, and paired each man with an equal number of positive and negative animals. In a memory test, participants reported more co-occurrences of same-valence man/animal pairs than opposite-valence pairs. This valence-compatibility effect occurred even when attitudes were induced after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
4
5
1
Order By: Relevance
“…In sum, the use of affect-as-information will increase the EC effect observed with CSs classified as “aware,” but will decrease the EC effect observed with CSs classified as “unaware.” This can explain the emergence of a reversed EC effect for unaware CSs observed by Stahl et al (2009; see also Förderer & Unkelbach, 2013). In addition, recent research has shown that participants do in fact rely on their feelings when answering contingency awareness questions (Bar-Anan & Amzaleg-David, in press), confirming the concerns raised in the simulation conducted by Hütter et al (2012).…”
Section: The Correlational Approach: From Participants To Css and Frosupporting
confidence: 62%
“…In sum, the use of affect-as-information will increase the EC effect observed with CSs classified as “aware,” but will decrease the EC effect observed with CSs classified as “unaware.” This can explain the emergence of a reversed EC effect for unaware CSs observed by Stahl et al (2009; see also Förderer & Unkelbach, 2013). In addition, recent research has shown that participants do in fact rely on their feelings when answering contingency awareness questions (Bar-Anan & Amzaleg-David, in press), confirming the concerns raised in the simulation conducted by Hütter et al (2012).…”
Section: The Correlational Approach: From Participants To Css and Frosupporting
confidence: 62%
“…If indeed contingency awareness does not increase the effect of pairing on evaluation, it might suggest that previous findings of positive correlation between contingency memory and evaluation did not reflect a causal relation with awareness as the cause and evaluation as the effect (for evidence of the opposite causal relation, see Amzaleg-David, 2014, andBar-Anan, De Houwer, &Nosek, 2010). The present results are incompatible with the propositional perspective on learning (Mitchell, De Houwer, & Lovibond, 2009).…”
Section: Discussioncontrasting
confidence: 90%
“…Such an inference process would also lead to a positive relationship for positively paired CSs and a negative relationship for negatively paired CSs. This interpretation is supported by previous work conducted by Bar-Anan and Amzaleg-David (2014), who showed that US valence memory measures can be biased by the evaluation of the CS (see also Hütter et al, 2012). Evidence in support of this alternative explanation would demonstrate a secondary influence of sampling decisions on evaluative learning.…”
Section: Discussionsupporting
confidence: 79%